AN ANALYSIS OF ID, EGO, AND SUPEREGO BY SIGMUND FREUD THROUGH KAT STRATFORD’S CHARACTER IN 10 THINGS I HATE ABOUT YOU MOVIE - Sheryl Norifly Loway; Nurochman (Jurnal Sosial Humaniora dan Pendidikan, 2023)
Personality is the part of us that sets us apart from others. In studying a personality, there are theories discussing the nature of every human being's personality, known as psychoanalysis theory. Psychoanalysis consists of three elements, namely ID, EGO, and SUPEREGO. These personalities are interconnected and create human behavior. The aims of this research are to find out Kat’s personality based on the Id, Ego, and Superego theory and to find out the most dominant personality in Kat Stratford’s character according to Sigmund Freud’s theory. This research uses a qualitative method. The data source is taken from scenes and dialogues in the 10 Things I Hate About You movie and focused on analyzing the Id, Ego, and Superego in Kat Stratford's character. The results of the analysis show that there are 16 data points for Id, 10 for Ego, and 3 for Superego, and the most dominant personality in Kat Stratford’s character is Id, with 16 data points.